مطالعہ سیرت النبی ﷺ: مسلم مورخین کے فکری اھداف: STUDY OF THE BIOGRAPHY OF THE PROPHET (ﷺ): THE INTELLECTUAL AIMS OF MUSLIM HISTORIANS (Al-Aasar, 2025)
There is no doubt that the key to success in both this world and the Hereafter lies in following the life and teachings of the Holy Prophet Muhammad ﷺ. His Seerah (biography) offers comprehensive guidance for every aspect of human life whether personal, social, spiritual, or moral leaving no area untouched. That is why Allah the Almighty has declared the Prophet’s ﷺ life as the ultimate and perfect model for all of humanity to follow. The Prophets (peace be upon them) were sent as beacons of guidance, and following their sayings and actions is the only path to salvation. What sets the Seerah of the Prophet Muhammad ﷺ apart is its timeless relevance and universality; it serves as a complete and practical example for all human beings until the Day of Judgment, without distinction of race, class, or era. Those who neglect or reject his Seerah will face severe consequences in the Hereafter, including disgrace and torment. The importance of studying and following the Seerah is further emphasized by its role as a living interpretation of the Quran, and the fact that no action is truly accepted by Allah unless it aligns with the Prophet’s ﷺ way. The noble companions (Sahabah) and revered scholars of Islam shaped their entire lives according to the Seerah, turning to it and the Quran for guidance in every matter, never showing the slightest neglect. For Muslims, the study of the Seerah is not merely historical it has deep spiritual goals: to attain the love of Allah, deepen love and understanding of the Prophet ﷺ, strengthen the desire to follow his path, implement his teachings in daily life, gain a true understanding of the religion, and develop a well-rounded Islamic character. Ultimately, adhering to the Seerah is a guaranteed path to success, peace, and honor in both this world and the eternal life to come.